FEATURES OF PERSIAN SOURCES ON THE HISTORY OF JOCHI ULUS (Journal of Oriental Studies, 2023)
he Ulus of Jochi, which arose in the 13th century in the steppes of Desht-Kypchak, paved the way for significant changes in the history of not only the Central Asian Turks, but also the peoples of Eastern Europe, the Urals and the Caucasus. The ulus of Jochi, which appeared on the stage of history after the reign of the Karakhanids, had its own history and culture, literature and written monuments. Therefore, the study of historical, literary heritage, even epigraphic, epitaphic, cartographic data relating to that era is of great importance. This opens the way to the study of the history of the Kazakh people through rethinking and scientific treatment from the point of view of the present day of each historical fact left by Western chroniclers and Eastern travelers regarding the Ulus of Jochi. In particular, the consideration of written monuments and historical data in the original Persian language and their use as scientific facts is one of the main problems that Oriental historians must take into account today. In the works written in Persian from the 13th to the 17th centuries, every written source relating to culture and written heritage, the official language and religion, the political and social structure and the administrative and administrative system of the Ulus Jochi is important. However, only with a critical look at these collected data and scientific study can one see the course of real historical events. Some of the historians who took place in the Khan's palaces may not be saturated with the real history of Ulus Jochi, or they may also distort the data for political reasons. For this, the collection, systematization and study of historical data written in Persian concerning the history of the Golden Horde is of great importance.